PERANCANGAN SISTEM ABSENSI KARYAWAN BERBASIS BIOMETRIK PADA CV X - Yuli Indah Fajar Dini; Amelia Amelia (Bajang Institute, 2026)
This community service activity was conducted at a company engaged in scrap metal processing and trading in Batam City. The company still utilized a manual attendance recording system through attendance books, which resulted in several challenges, including inaccurate attendance records, difficulties in monitoring employee attendance, and delays in attendance data recapitulation. These conditions affected the effectiveness of attendance management and employee discipline supervision within the company. This activity aimed to design a biometric-based employee attendance system to support a more accurate, structured, and efficient attendance management process. The method employed was direct observation of attendance recording procedures and attendance data management practices within the company. The findings from the observation were analyzed to identify existing problems and formulate system requirements for the proposed attendance system. The outputs of this activity included user requirement identification, system flowcharts, system blueprints, and employee attendance recap formats. The proposed biometric-based attendance system is expected to improve the accuracy of attendance records, facilitate attendance monitoring, and support employee discipline evaluation in a more structured manner. Furthermore, the system design can serve as a reference for the future development and implementation of a more effective attendance management system.